TRPC3-mediated Ca2+ entry contributes to mouse airway smooth muscle cell proliferation induced by lipopolysaccharide. Issue 4 (October 2016) - Chen, Xiao-Xu; Zhang, Jia-Hua; Pan, Bin-Hua; Ren, Hui-Li; Feng, Xiu-Ling; Wang, Jia-Ling; Xiao, Jun-Hua
Graphical abstract: Highlights: LPS induced airway smooth muscle cells (ASMCs) proliferation. LPS enhanced TRPC3 protein expression, NSCC currents, resting and ACh-elicited [Ca 2+ ]i . Blockade and gene silencing of TRPC3 inhibited LPS-induced ASMCs proliferation. TRPC3-mediated Ca 2+ entry contributes to LPS-induced ASMCs proliferation. Abstract: Airway remodeling is a histopathological hallmark of chronic respiratory diseases that includes airway smooth muscle cell (ASMC) proliferation. Canonical transient receptor potential channel-3 (TRPC3)-encoded nonselective cation channels (NSCCs) are important native constitutively active channels that play significant roles in physiological and pathological conditions in ASMCs. Lipopolysaccharides (LPSs), known as lipoglycans and endotoxin, have been proven to be inducers of airway remodeling, though the mechanisms remain unclear. We hypothesized that TRPC3 is important in LPS-induced airway remodeling by regulating ASMC proliferation. To test this hypothesis, mouse ASMCs were cultured with or without LPS for 48 h. Cell viability, TRPC3 protein expression, NSCC currents and changes in intracellular calcium concentration ([Ca 2+ ]i ) were then analyzed using an MTT assay, western blotting, whole-cell patch clamp and calcium imaging, respectively. The results showed that LPS treatment significantly induced ASMC proliferation, up-regulation of TRPC3 protein expression and enhancement of NSCC currents, resting [Ca 2+ ]i and ACh-elicited changes in [Ca 2+ ]i . TRPC3 blocker Gd 3+, TRPC3 blocking antibody or TRPC3 gene silencing by siRNA significantly inhibited LPS-induced up-regulation of TRPC3 protein, enhancement of NSCC currents, resting [Ca 2+ ]i and ACh-elicited changes in [Ca 2+ ]i, eventually inhibiting LPS-induced ASMCproliferation. These results demonstrated that TRPC3-mediated Ca 2+ entry contributed to LPS-induced ASMC proliferation and identified TRPC3 as a possible key target in airway remodeling intervention.